Polymorphism of SERPINE2 gene is associated with pulmonary emphysema in consecutive autopsy cases - Kida Kozui; Ishii Takeo; Kumasaka Toshio; Tanaka Noriko; Arai Tomio; Ikeda Shinobu; Fujimoto Koichi; Muramatsu Masaaki; Sawabe Motoji (BMC, 2010)
Abstract Background The SERPINA1, SERPINA3, and SERPINE2 genes, which encode antiproteases, have been proposed to be susceptible genes for of chronic obstructive pulmonary disease (COPD) and related phenotypes. Whether they are associated with emphysema is not known. Methods Twelve previously reported single nucleotide polymorphisms (SNPs) in SERPINA1 (rs8004738, rs17751769, rs709932, rs11832, rs1303, rs28929474, and rs17580), SERPINA3 (rs4934, rs17473, and rs1800463), and SERPINE2 (rs840088 and rs975278) were genotyped in samples obtained from 1,335 consecutive autopsies of elderly Japanese people. The association between these SNPs and the severity of emphysema, as assessed using macroscopic scores, was determined. Results Emphysema of more than moderate degree was detected in 189 subjects (14.1%) and showed a significant gender difference (males, 20.5% and females, 7.0%; p < 0.0001). Among the 12 examined SNPs, only rs975278 in the SERPINE2 gene was positively associated with emphysema. Unlike the major alleles, homozygous minor alleles of rs975278 were associated with emphysema (odds ratio (OR) = 1.54; 95% confidence interval (CI) = 1.02-2.30; p = 0.037) and the association was very prominent in smokers (OR = 2.02; 95% CI = 1.29-3.15; p = 0.002). Conclusions SERPINE2 may be a risk factor for the development of emphysema and its association with emphysema may be stronger in smokers.